2016
DOI: 10.1542/peds.2015-1353
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Phototherapy and Infantile Cancer

Abstract: OBJECTIVE: To determine whether neonatal phototherapy is associated with cancer in the first year after birth. METHODS:We analyzed a data set from the California Office of Statewide Health Planning and Development that was created by linking birth certificates, death certificates, and hospital discharge abstracts up to age 1 year. Subjects were 5 144 849 infants born in California hospitals at ≥35 weeks' gestation from 1998 to 2007. We used International Classification of Diseases, Ninth Revision codes to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 36 publications
0
81
0
6
Order By: Relevance
“…One key confounder is Down syndrome. In both the California Late Impact of Phototherapy Study 20 and the current study, Down syndrome was associated not only with a markedly increased risk of leukemia but also a fivefold increase in the use of phototherapy. As reported in previous studies, other chromosomal and congenital anomalies 26 and low 5-minute Apgar score 27 were also associated with certain types of cancer and were associated with higher phototherapy rates.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…One key confounder is Down syndrome. In both the California Late Impact of Phototherapy Study 20 and the current study, Down syndrome was associated not only with a markedly increased risk of leukemia but also a fivefold increase in the use of phototherapy. As reported in previous studies, other chromosomal and congenital anomalies 26 and low 5-minute Apgar score 27 were also associated with certain types of cancer and were associated with higher phototherapy rates.…”
mentioning
confidence: 50%
“…In the California Late Impact of Phototherapy Study, which used linked birth certificates and discharge abstracts, Wickremasinghe et al 20 reported statistically significant propensity-adjusted ORs for any cancer, myeloid leukemia, kidney, and other cancer diagnoses before age 1 year. A limitation of that study is that follow-up was only 1 year, raising the question of whether the increased risk persists.…”
mentioning
confidence: 99%
“…Specifically, the risk for myeloid leukemia and kidney cancer seemed slightly increased. However, after correcting for congenital and chromosomal abnormalities, the associations were no longer statistically significant [17,18]. Additionally, previous studies could not find an association between phototherapy and skin cancer [16,19].…”
Section: Intensive Phototherapymentioning
confidence: 84%
“…Some physicians may even initiate phototherapy at bilirubin levels below phototherapy limits because of the few adverse effects and convenient application. In some current publications, phototherapy has been shown to be related with increased risk of childhood and infancy cancers (21). It may be thought that the increase in the risk of cancer is related with the long-term results of the genotoxic effect of phototherapy or hyperbilirubinemia itself.…”
Section: Discussionmentioning
confidence: 99%